2011
DOI: 10.1111/j.1469-7580.2011.01398.x
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of 3D osteon morphology by synchrotron radiation micro‐CT

Abstract: Cortical bone histology has been the subject of scientific inquiry since the advent of the earliest microscopes. Histology -literally the study of tissue -is a field nearly synonymous with 2D thin sections. That said, progressive developments in high-resolution X-ray imaging are enabling 3D visualization to reach ever smaller structures. Micro-computed tomography (micro-CT), employing conventional X-ray sources, has become the gold standard for 3D analysis of trabecular bone and is capable of detecting the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 62 publications
(123 reference statements)
1
40
0
Order By: Relevance
“…phase contrast) in order to directly evaluate osteon geometry in 3D (Cooper et al. ). A greater appreciation of the morphological variation of osteons opens the door to more rigorous exploration of what factors underpin this variation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…phase contrast) in order to directly evaluate osteon geometry in 3D (Cooper et al. ). A greater appreciation of the morphological variation of osteons opens the door to more rigorous exploration of what factors underpin this variation.…”
Section: Discussionmentioning
confidence: 99%
“…) or synchrotron‐based micro‐CT imaging (Cooper et al. ). As noted for serial section‐based studies, imaging‐based studies have also revealed great complexity and variation in 3D osteon structure – but they, too, have yielded largely qualitative insights so far.…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade, SR micro-CT has been used for the simultaneous assessment of structure and mineralization in human or animal trabecular bone [42,43]. Its application to cortical bone also permits quantification of the Haversian canal network and visualize osteons [34,44,45].…”
Section: Ct Techniquesmentioning
confidence: 99%
“…104 New imaging techniques now make it possible to investigate the detailed 3D structure of individual osteons in the femoral cortex and the anatomical relationships between them. 105,106 These offer new avenues for understanding how conversion of the cortex to trabecular bone, leading to cortical thinning, 104,107 develops and to how osteonal structures might help preserve the toughness of bone once a crack threatens to expand beyond the osteon's own territory. 108 Another cause of increased remodelling is the secondary hyperparathyroidism associated with reduced vitamin D levels, commonly seen in the elderly.…”
Section: Remodelling and Fracture Riskmentioning
confidence: 99%